ANALISIS PELAKSANAAN NILAI-NILAI TOLERANSI BERAGAMA PADA MASYARAKAT DI RT 001 RW 001 KELURAHAN SUKAHARJA KECAMATAN DELTA PAWAN KABUPATEN KETAPANG - Safitri, Tri Endarti Rahma; Bahari, Yohanes; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of this study was to determine the implementation of religioustolerance values in the community in RT 001 RW 001, Sukaharja Village, DeltaPawan District, Ketapang Regency. The sub-problem in this research is how toimplement the values of tolerance in the aspect of giving freedom of worship,respecting each other's beliefs and understanding each other. The research methodused is descriptive in the form of qualitative research. The source of this researchdata is the community in RT 001 RW 001, Sukaharja Village, Delta Pawan District,Ketapang Regency. The data collection technique is through interviews anddocumentation, while the data collection tool uses observation and interviewguidelines, observation and documentation. The research analysis was presentedin a qualitative descriptive manner using four informants. The results of this studyindicate that there is an implementation of tolerance values from the aspect ofgiving freedom of worship, mutual respect for beliefs, and mutual understandingbetween religions adopted in RT 001 RW 001, Sukaharja Village, Delta PawanDistrict, Ketapang Regency.Keywords: Implementation, Tolerance Value, Religious Tolerance